NURSING STUDENTS' KNOWLEDGE ABOUT PATIENT SAFETY - Prodalima Prodalima; Delfriana Ayu Astuty; Elpriska Elpriska (Universitas Galuh, 2026)
Patient safety is an essential competency that nursing students must develop during their educational training. This study aimed to describe the level of patient safety knowledge among students of the Diploma in Nursing Program at Universitas Bunda Thamrin based on three main components: patient safety culture, risk management and incident reporting systems, and effective communication and patient engagement. A descriptive quantitative cross-sectional design was conducted among 39 nursing students selected using accidental sampling. The study was carried out at the Diploma in Nursing Program of Universitas Bunda Thamrin from October to November 2025. Data were collected using a structured questionnaire consisting of 15 statements, with five items representing each patient safety component. The results showed that 85% of respondents had a good level of patient safety knowledge, while 15% had a moderate level. All respondents (100%) demonstrated high agreement with key statements related to patient safety culture, non-punitive incident reporting, and the importance of effective communication and patient involvement. These findings indicate that nursing students possess a strong foundational understanding of patient safety; however, this knowledge remains primarily cognitive. Practically, the results highlight the need to strengthen patient safety education through clinically oriented learning approaches and simulation-based training to bridge the gap between knowledge and practice.